Limestone – A Versatile Mineral In Agriculture - J. Bleeck; G. Mahrt (Society for Mining, Metallurgy & Exploration, 2006)
INTRODUCTION Many excellent papers have been written and presented regarding agricultural lime and the subject has been covered extensively in books concerning soil science, fertilizing, limestone, etc. We felt challenged to construct a paper that wouldn’t merely be a repetition of past presentations. Therefore, we chose to begin with factors having the most impact on plant growth realizing that the audience is likely to be relatively unfamiliar with this subject. So, we decided to dig deep into the roots of soil and plant growth science in order to better understand the significant role of limestone in this important area. The soil with the higher plants growing upon it forms an open and dynamic ecosystem in which there is flux of energy and material (heat, light, water, nutrients, mineral and organic matter, organisms). Plants root in the soil and then take up oxygen for root respiration, yielding energy for nutrient uptake, water for turgescence and transpiration and use in photosynthesis and the mineral nutrients needed for the synthesis of organic matter. Above the ground the plant takes in light energy and heat using them in photosynthesis to assimilate atmospheric CO2. Photosynthesis is the basic life process of creation. However, we will look at the root room where soil, water, air, and heat economy and the supply of nutrients determine soil fertility and the important role lime plays here. Location is the primary point to be considered when discussing agriculture (climate and soil); secondly, the dynamic and mobility of the minerals (plant nutrients) in the soil; and thirdly the conversion of organic substances into humus. And then there is a great deal of water involved in the growing process. In order to produce 1 kg of dry plant substance, 300 to 800 kg of water must be pumped through the plant and is then lost by transpiration. Cereals, vegetables, and sugar beets consume between 400 to 500 kg of water during the growing process and long-growing crops, such as alfalfa and clover, can consume 600 to 800 kg of water per kg of finished product. Without water, a plant cannot grow. (Reference 1)